2015
DOI: 10.1161/strokeaha.115.010260
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach to Lysis Utilizing Eptifibatide and Recombinant Tissue-Type Plasminogen Activator in Acute Ischemic Stroke-Full Dose Regimen Stroke Trial

Abstract: Background and Purpose The Combined Approach to Lysis Utilizing Eptifibatide and rt-PA in Acute Ischemic Stroke (CLEAR) and CLEAR-Enhanced Regimen (CLEAR-ER) trials demonstrated safety of reduced dose recombinant tissue plasminogen activator (rt-PA) plus the glycoprotein 2b/3a inhibitor, eptifibatide, in acute ischemic stroke (AIS) compared to rt-PA alone. The objective of the CLEAR-Full Dose Regimen (CLEAR-FDR) trial was to estimate the rate of symptomatic intracerebral hemorrhage (sICH) in AIS patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…We feel this is an advantage of the design as it adds to the building evidence of medical adjunctive antithrombotic amplification of IV-rt-PA. 6,24 After terminating the trial at 90 patients, we tested the feasibility and explored safety and reperfusion outcomes in a small cohort treated with IV-rt-PA, high-dose argatroban and endovascular therapy in 0–6 hour AIS with large vessel occlusion (clinicaltrials.gov NCT02448069). The results will be reported separately but demonstrated the feasibility and safety of combining the ARTSS-2 protocol with endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…We feel this is an advantage of the design as it adds to the building evidence of medical adjunctive antithrombotic amplification of IV-rt-PA. 6,24 After terminating the trial at 90 patients, we tested the feasibility and explored safety and reperfusion outcomes in a small cohort treated with IV-rt-PA, high-dose argatroban and endovascular therapy in 0–6 hour AIS with large vessel occlusion (clinicaltrials.gov NCT02448069). The results will be reported separately but demonstrated the feasibility and safety of combining the ARTSS-2 protocol with endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…ancillary drug therapies such as argatroban or eptifibitide. 27,28 Nonpermeable thrombi recanalize more slowly and less commonly and may require mechanical means to disrupt the thrombus and increase surface area for enzymatic access with therapies such as ultrasound. 29 Clinical trial design of novel thrombolytic or ancillary reperfusion treatments might therefore be optimized using the expected recanalization prevalence data from this study.…”
Section: No Residual Flowmentioning
confidence: 99%
“…However, reperfusion was not commonly evaluated. We look forward to new studies that will reexamine the neuroprotection hypothesis in an era of proven early reperfusion 83) . The glycoprotein IIb/IIIa receptor antagonists (GPIs) in terms of platelet inhibition eptifibatide have demonstrated that AIS patients with tPA plus eptifibatide showed lower incident rates of symptomatic HT than those with tPA alone.…”
Section: Combination Treatments With Protective Agentsmentioning
confidence: 99%